THE RAPID CULTURE METHOD FOR THE INDICATION OF RABIES VIRUS ANTIGEN IN INFECTED CELL CULTURES - E. P. Barkova; F. G. Nagieva; V. G. Nikulina; A. N. Lisakov (Инфекция и иммунитет, 2014)
Abstract. The rapid culture method for the indication of antigens of rabies virus has been improved. It allows to detect the antigen of rabies virus within 5 hours from the moment the cell cultures was infected. To achieve this aim it is necessary to use cell culture BHK-F, polyclonal antirabies FITC labelled immunoglobulin and direct method of membrane immunofluorescense. Applying of twofold freshly filtrated 3% paraformaldehyde as fixing solution allows to detect early virus proteins of rabies virus.